State aid, industrial restructuring and privatization in the new German Länder: competition policy with case studies of the shipbuilding and synthetic fibres industries - Lars-Hendrik Röller; Christian von Hirschhausen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
This paper analyzes the effects of state aids in East Germany on European competition. We first discuss the specificity of post-socialist industrial restructuring in East Germany, which consisted of the enterprization of socialist combines into capitalist enterprises. Second, we review the economic rationale for state aids in the East German context by distinguishing between static and dynamic arguments. Third, we apply these theoretical arguments for state aid to two concrete case studies: shipbuilding and synthetic fibres. We conclude from a static point of view that state aids can not be justified in both cases: large capacities were added to already existing overcapacities in Europe. Considering dynamic arguments, we assess the likelihood that the industrial restructuring may lead to the creation of new East German enterprises that are at the leading edge of technology and with a high productivity. While the East German cases of state aid were a novelty for European competition policy, there might be important implications for other postsocialist countries (e.g. Poland, Hungary, Czech and Slovak Republic) once they join the EU. – – In diesem Beitrag untersuchen wir die wettbewerbspolitischen Auswirkungen der Industriereformen in den neuen Bundesländern. Eingangs wird die post-sozialistische Besonderheit dieses Prozesses erläutert, die in der Unternehmisierung sozialistischer VEBs in marktwirtschaftliche Unternehmen bestand. Im Anschluß daran werden statische und dynamische Kriterien zur Bewertung staatlicher Beihilfen entwickelt. Diese werden anhand von zwei Fallstudien getestet (Schiffbau und Synthesefasern). In beiden Fällen erscheinen die staatlichen Beihilfen aus statischer Sicht problematisch, da mit hohem finanziellem Aufwand neue Kapazitäten geschaffen wurden, die das Problem der europäischen Überkapazitäten noch verschärften. Bei dynamischer Sichtweise fällt das Ergebnis positiver aus, da die ostdeutschen Unternehmen bei erfolgreich abgeschlossener Umstrukturierung zu den europaweit produktivsten gehören könnten. Die Erfahrung in den neuen Bundesländern deutet auch darauf hin, daß bei einer EU-Erweiterung um mittel- und osteuropäische Länder erhebliche wettbewerbspolitische Probleme zu erwarten sind.
Keywords: 330